Book Reviews - Julie Nichols; Peter Fields; Walter L. Reid; Jeffrey H. Taylor; Warren Hatch (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Julie Nichols - Reading Ethically Peter Fields - Gregory Marshall. Shaped by Stories: The Ethical Power of Narratives. Notre Dame, IN: U of Notre Dame P., 2009 Walter L. Reed - Gregory, Marshall. Teaching Excellence in Higher Education, ed. Melissa Valiska Gregory. NY: Palgrave Macmillan, 2013 Jeffrey H. Taylor - Musgrove, Laurence. Local Bird. Beaumont, TX: Lamar U Press, 2015 Warren Hatch - Lynch, Tom, Cheryll Glotfelty, Karla Armbruster. The Bioregional Imagination—Literature, Ecology, and Place. Athens, GA: U of GA Press, 2012